GAMBARAN PENGELOLAAN DAN UJI KUALITAS LIMBAH CAIR DI UPTD PUSKESMAS BANJARMANGU 2 - Enjelika Dwi Rosania; Bayu Suseno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2025)
The Wastewater Treatment Plant (IPAL) plays a crucial role in preventing environmental pollution caused by liquid waste from healthcare services in community health centers. However, many IPAL units in primary healthcare facilities still operate suboptimally. This study aimed to describe the management of the IPAL and the results of physicochemical wastewater testing at UPTD Banjarmangu 2 Public Health Center, as well as to evaluate its compliance with the quality standards based on Regulation of the Minister of Environment and Forestry No. P.68 of 2016. This descriptive research used a cross-sectional approach. Data were collected through direct observation, pH and flow rate measurements using measuring instruments, and laboratory tests for BOD, COD, ammonia, and TSS. Wastewater samples were taken three times from the IPAL outlet using grab sampling. The results showed that eight out of nine IPAL components met technical standards, except for the absence of a grease trap. All laboratory test parameters met the quality standards: pH (7.6–8), BOD (15–18 mg/L), COD (25–29 mg/L), ammonia (<0.03 mg/L), TSS (17–20 mg/L), and flow rate (73–79 L/person/day). It is concluded that the IPAL at UPTD Banjarmangu 2 has met the required quality standards. It is recommended to install a grease trap and conduct regular laboratory tests to maintain IPAL performance and prevent environmental pollution.